Implementing Solar Energy For Watering Plantation In Kepel Village, Kare District, Madiun Regency - Khusnul Arifin; Riny Sulistyowati (Procedia of Engineering and Life Science, 2022)
Drought refers to a condition in which supply of water at a certain area gets decreasing. This sort of condition also occurs in Kepel Village, Kare District, Madiun Regency. During the dry season, the farmers who have land on the hilly area around the slope of Mount Wilis encounter difficulties in watering their plantation. The condition becomes worse as the plantation land is located at the mountain slope which is far from electricity access provided by PLN, while the source of water is below their land. To overcome this problem, PV can be used as a device to produce electrical energy due to several advantages such as environmentally friendly, low maintenance cost, and zero emission. Furthermore, the energy required for PV is always available in the nature or can be renewed (renewable energy). Hence, PV belongs to a solution for electrical source to generate a water pump. Since the pump needs AC source in 220V and 50Hz, the researcher developed an inverter through SPWM (Sinusoidal Pulse Width Modulation) method for changing DC current 24V to AC current 220 and 50Hz. In this context, the inverter was regulated in 290V AC and 51.150 Hz and when the water pump load 125W was given, the voltage gained 225V AC. The drop of voltage occurred because the load was induction motor. The results of testing this solar energy power station demonstrated that the water pump could fill the water reservoir 70l within 3.8 minutes and could water 1 are land. This test was carried out for 10 days at 08.00 am as it is the optimum sun light and the proper watering time for farmers.